Water requirement and levels of irrigation of banana FHIA-18 in the semiarid region of Piauí state - D'Albuquerque Junior, Boanerges Siqueira [UNESP]; Gomes, Edilson Ramos [UNESP]; de Sousa, Valdemício Ferreira [UNESP]; Sousa, Antonio de Pádua [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2013)
This study aimed at determining the cultivation coefficient of banana cv. FHIA-18 and establishing levels of irrigation for the 2° and 3° cycle capable of raising productivity and fruit quality in the environmental conditions of the semiarid region of Piaui state. The experiment was carried out in the Pilot Project of Irrigated Fruit of the Parnaíba Valley located in the city of Santa Rosa do Piauí. The experimental design was randomized blocks with 6 treatments (levels of irrigation estimated from percentages of ETo) with 4 replications. Each plot consisted of 3 rows with 13 plants; side lines were borders to measure the morphological and physiological characteristics. A total of four plants were used per plot. The treatments consisted of applying water blades based on daily ETo: T1=25% ETo; T2=50% ETo; T3=75% ETo; T4=100% ETo; T5=125% ETo and T6=150% ETo. Crop coefficients of the 2nd and 3rd cycle for the vegetative and reproductive stages were 1.03 and 1.05, respectively; and higher yield and better fruit quality were obtained by applying water depths between 1600 and 1800 mm per cycle.
Necessidade hídrica e lâminas de irrigação da bananeira cv. FHIA-18 na região semiárida do Piauí
Keywords: Crop coefficient; Musa acuminata L.; Productivity